CORTISOL DAY CURVE TO GUIDE GLUCOCORTICOID REPLACEMENT IN A PATIENT WITH ADRENAL INSUFFICIENCY ON ANTI-TUBERCULOSIS THERAPY - Khoo, Jun Kit; Sarvanandan, Tharsini; Ooi, Ying Guat; Hee, Nicholas Ken Yoong; Lim, Quan Hziung; Paramasivam, Sharmila; Vethakkan, Shireene; Ratnasingam, Jeyakantha (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Hydrocortisone in divided doses (typically 15 – 25 mg/day) is the most common form of glucocorticoid replacement regimen in patients with adrenal insufficiency (AI). However, this may be inadequate for patients on CYP3A4 inducers which affect glucocorticoid metabolism. While there are no specific guidelines on dose adjustment, cortisol day curve (CDC) could be used to guide optimal replacement. We report a case of a female with AI secondary to pituitary tuberculosis requiring hydrocortisone dose adjustment following initiation of anti-tuberculosis therapy (anti-TB). CASE A 45-year-old female presented with a worsening headache for a month, without any constitutional symptoms. Imaging revealed a heterogenous sellar mass (1.3 x 1.5 x 2.1 cm) without chiasmal compression or cavernous involvement. Blood investigations showed serum cortisol <14 nmol/L (reference interval 145-619), FT4 10 pmol/L (reference interval 11.5 – 22.7) and TSH <0.01 m IU/L (reference interval 0.55-4.78). Other blood investigations were normal. She was commenced on hydrocortisone 10 mg BD (8 am, 2 pm) and levothyroxine 50 mcg OD. Trans-sphenoidal resection was performed, and histopathology revealed necrotising granulomatous inflammation with caseating necrosis. The diagnosis of pituitary tuberculosis was made, and first line anti-TB drugs (rifampicin, isoniazid, pyrazinamide, and ethambutol) were initiated. Despite pre-emptively increasing hydrocortisone to 20 mg BD, she experienced postural hypotension, lethargy, and nausea soon after initiation of anti-TB medications, especially in the early afternoon and evening. Cortisol day curve was done by measuring serum cortisol hourly from 8 am – 8 pm while she took her regular hydrocortisone 20 mg BD. Serum cortisol levels were <14 nmol/L (8 am), 1009 nmol/L (9 am), 664 nmol/L (10 am), 386 nmol/L (11 am), 217 nmol/L (12 pm), 88 nmol/L (2 pm), 761 nmol/L (3 pm), 857 nmol/L (4 pm), 521 nmol/L (5 pm), 256 nmol/L (6 pm), and 85 nmol/L (8 pm). Hydrocortisone was adjusted to 20 mg (8 am), 10 mg (1 pm) and 5 mg (6 pm) to counter the trough levels. This led to a marked improvement in her symptoms. CONCLUSION CYP3A4 inducers (anti-TB) affect glucocorticoid metabolism and replacement in patients with AI. The cortisol day curve could be used as a guide to tailor therapy in situations where adequate replacement doses and timing are not easily identified.